Optical, elastical and piezooptical properties of the β-BaB2O4 and Li2B4O7 borate crystals - Adamiv, V. T.; Burak, Ya. V.; Martynyuk-Lototska, I. Yu.; Kostyrko, M. E.; Vlokh, R. O.; Romanyuk, G. M.; Shranz, W. (Видавництво Національного університету «Львівська політехніка», 2002)
The optical, elastic and piezooptical properties of the borate crystals have been investigated. The dispersions of the indexes refraction of the Li2B4O7 crystals have been determinated in wavelength range 350 - 650 nm. The results of the measurement velocity of the longitudinal and transverse ultrasonic waves on borate crystals are presented. Using ultrasonic velocity measurements the components of the elastic matrix Cmn of these crystals have been determined. Using the determined values of the elastooptical tensor components the acoustooptical quality M2 of β-BaB2O4 crystals has been calculated
Keywords: borate crystal; optical and piezooptical properties